Problem-Solving Ability with the Implementation Guided Discovery Model on Excretory System Material in Class XI of SMA Negeri 18 Medan - Morina Wati; Melva Silitonga (FMIPA UNNES, 2023)
One of the demands of 21st-century learning is optimizing students' problem-solving abilities. The problem-solving ability of students at SMA Negeri 18 Medan is still low. One of the contributing factors to low problem-solving ability is the lack of application of learning devices and models that can activate students and are still teacher-centered. One learning model that can improve problem-solving skills is the guided discovery model. This study aims to analyze students' problem-solving abilities with the implementation of the guided discovery model, the implementation of guided discovery syntax in learning, and student responses to the guided discovery model on excretory system material. This type of research is quasi-experimental research with a pretest-posttest control group design. Sampling using random sampling technique, XI IPA 1 as guided discovery class and XI IPA 2 as direct instruction class. The instruments used consist of essay questions on problem-solving skills, syntax implementation observation sheets, and student response questionnaires. The data obtained are first tabulated, searched for averages, and then analyzed by normality tests and independent sample t-tests. From the results of the independent sample t-test, a significance value of 0.000<0.05 was obtained, indicating that students' problem-solving abilities with guided discovery models and direct instruction models differed significantly. The results showed that the problem-solving ability of grade XI students of SMA Negeri 18 Medan who were taught using the guided discovery model was very high (82.69), the implementation of the guided discovery model syntax with a percentage of 99%, and student responses to learning showed a positive response. Based on the results of the study, the guided discovery model is very appropriate to be used in training the problem-solving ability of grade XI students at SMA Negeri 18 Medan on excretory system material.